An increase in mean platelet volume (MPV) as a predictor of mortality in children with sepsis - Rianti Puji Lestari; Sumadiono Sumadiono; Eggi Arguni (Universitas Gadjah Mada, 2022)
Sepsis is associated with increased morbidity and mortality in children worldwide, mainly in developing countries. This fatal risk emphasizes the importance of finding accessible and inexpensive parameters to be used as predictors for mortality in children with sepsis. The aim of this study was to determine the role of increased mean platelet volume (MPV) as a predictor for mortality in children with sepsis. A case control study was applied using medical records of all in-patients aged 1 mo -18 y diagnosed with sepsis at Dr. Sardjito General Hospital, Yogyakarta from January 2015-December 2016. Bivariate and multivariate analyses by Chi-square and logistic regression to evaluate the correlations between increased MPV within the first 24-72 h (ΔMPV>0) and mortality were applied. Eighty-one eligible subjects met the inclusion/exclusion criteria with the mortality was 52%. Chi-square analysis showed significant correlations between increased MPV and mortality (p=0.005). Multivariate analysis showed increased MPV within the first 24-72 h after sepsis diagnosis as a predictor for mortality after controlling for sex and AKI (adjusted OR 3.851; 95% CI:1.354-10.948; p= 0.011). In conclusion, an increase in MPV within the first 24-72 h after diagnosed is an independent predictor for mortality in children with sepsis.